Development of the credit market of Ukraine under macroeconomic instability - Dubyna, Maksym; Popelo, Olha; Zhavoronok, Artur; Lopashchuk, Inna; Fedyshyn, Maiia (LLC “Consulting Publishing Company “Business Perspectives”, 2023)
The development of Ukraine’s credit market occurs under periodic economic crises. Available destructive processes inhibit the development of credit relations, negatively affecting the lending of economic entities and restraining the development of the national economy. This study aims to highlight the basic transformations in the development of the credit market of Ukraine, which are formed in macroeconomic instability. The economic development trends in Ukraine were assessed using classical statistical methods. The correlation regression analysis was used to analyze the influence of macroeconomic parameters (exchange rate, average salary, and cost of loans) on the volume of bank lending. The results show that the national economy of Ukraine during 2005–2021 developed in the conditions of periodic macroeconomic instability, and the pre-crisis (an indicator of 2013) parameters of bank lending volumes have not restored within the credit market. The paper stresses the significant impact of the COVID-19 pandemic: in 2020, the volume of bank lending decreased by 10.38 billion USD. Moreover, the econometric analysis of the influence of specific macroeconomic parameters (exchange rate, average salary, and cost of loans) on the development of bank lending in Ukraine demonstrated that the stability of the national currency exerts the greatest influence on the lending processes of economic entities in Ukraine. Its provision in the long term allows the creation of favorable conditions for the credit market functioning after the shock periods.
Keywords: bank lending; credit institutions; credit relations; macroeconomic development; macroeconomic instability; national economy